Head injury instructions: a time to unify. Issue 4 (July 1997) - Parsley, J; Fletcher, L; Mabrook, A F
Abstract : OBJECTIVE: To compare and contrast the head injury advice give by various hospitals in England after minor head injury, and to draw attention to the need for a national set of head injury instructions. METHODS: 50 accident and emergency departments were contacted by post and asked to supply a copy of their head injury information card or leaflet; 41 hospitals replied (82%). RESULTS: Comparison of the cards showed inconsistencies and conflicting advice given by the departments contacted. CONCLUSIONS: There is a need for a national head injury card and a proposal for such a card is presented.